Implementing a social-ecological systems framework for conservation monitoring: lessons from a multi-country coral reef program. (December 2019) - Gurney, Georgina G.; Darling, Emily S.; Jupiter, Stacy D.; Mangubhai, Sangeeta; McClanahan, Tim R.; Lestari, Peni; Pardede, Shinta; Campbell, Stuart J.; Fox, Margaret; Naisilisili, Waisea; Muthiga, Nyawira A.; D'agata, Stephanie; et al.
Abstract: Multi-scale social-ecological systems (SES) approaches to conservation and commons management are needed to address the complex challenges of the Anthropocene. Although SES approaches to monitoring and evaluation are advocated in global science and policy arenas, real-world applications remain scarce. Here, we describe the first operationalization and implementation of Ostrom's influential SES framework for monitoring practice across multiple countries. Designed to inform management aimed at sustaining coral reefs and the people that depend on them, we developed our SES monitoring framework through a transdisciplinary process involving academics and practitioners with expertise in social and ecological sciences. We describe the SES monitroing framework, including how it operationalizes key insights from the SES and program evaluation literatures, and demonstrate how insights from its implementation in more than 85 communities in four countries (Fiji, Indonesia, Kenya and Madagascar) are informing decision-making at multiple levels. Responding to repeated calls for guidance on applying SES approaches to monitoring and management practice, we outline the key steps of the transdisciplinary development of the framework and lessons learnt. Therefore, our work contributes to bridging the gap between SES science and commons management practice through not only providing an SES monitoring framework that can be readily applied to coral reefs and other commons, but also through demonstrating how to operationalize SES approaches for real-world monitoring and management practice.